PENDAMPINGAN IMPLEMENTASI PRINSIP 4P BAURAN PEMASARAN DALAM UPAYA MENINGKATAKAN OMZET PADA IKM YAWEI PUDU DI TASANGKAPURA KELURAHAN JAYAPURA SELATAN - Diana Yulia Paula; Agustina Ester Antoh; Endah Dwi Lestari; Yoseb Boari Yobo; Risky Mayor; Resini Handayani E. Binur (Gapenas Publisher, 2023)
One of the steps that can be taken to create value for customers is the marketing mix program, namely product, price, place, and promotion or 4P. Proper management of the marketing mix will provide many benefits for business actors. The marketing mix can be a distinct advantage for business actors that is not owned by its competitors. The purpose of community service is to help IKM Yawei Pudu, Tasangkapura in Jayapura Selatan Village to implement the 4P principles of the marketing mix in an effort to increase sales turnover during the Covid-19 pandemic. The results of the implementation of the 4P principles of the marketing mix in an effort to increase sales turnover to Yawei Pudu IKM players in Jayapura Selatan Village include; 1). Products: quality, design, shape, brand, and product packaging are still not given proper attention. 2). Price: still not taking into account the expenses, production costs and well-earned profits so the pricing seems high. 3). Marketing/location distribution channels: the place of business is still not in a more strategic location. And 4). Promotion: promotional activities have not been carried out optimally